The Readiness of Single-Specialty Hospitals in Isfahan to Attract Medical Tourists - Nasrin Shaarbafchi Zadeh; Asal Sadat Niaraees Zavare; Atefeh Najafi Shahkoohi; Behrooz Madahian (Kerman University of Medical Sciences, 2018)
The Readiness of Single-Specialty Hospitals in Isfahan to Attract Medical Tourists   Shaarbafchi Zadeh Nasrin1, Niaraees Zavare Asal Sadat2*, Najafi Shahkoohi Atefeh3, Maddahian Behrooz2 1. Assistant Professor, Health Management and Economics Research Center, Isfahan University of Medical Sciences, Isfahan, Iran 2. MSc in Health Services Management, Student Research Committee, School of Management and Medical Information, Isfahan University of Medical Sciences, Isfahan, Iran 3. MSc in Health Economy, Student Research Committee, School of Management and Medical Information, Isfahan University of Medical Sciences, Isfahan, Iran *Correspondence: School of Management and Medical Information, Isfahan University of Medical Sciences, Hezar Jerib Avenue, Isfahan  Tel: 00983136823663                                              Email: asal7447@gmail.com Abstract: Background & Objectives: Medical Tourism is one form of health services export that has attracted much attention. This industry has positive outcomes, including increased health services exports, increased foreign exchange earnings, brain drain prevention, increased employment of health workers, and reduced outflow of patients from the country. The purpose of this study was to investigate the readiness of single-specialty hospitals affiliated to Isfahan University of Medical Sciences to attract medical tourists. Methods: This is a descriptive cross-sectional study that was conducted in two single-specialty hospitals affiliated to Isfahan University of Medical Sciences in 2017. Data were collected using a checklist developed by the Ministry of Health. This checklist consisted a total of 80 questions and 5 dimensions such as human resources, hoteling, process, general conditions, and information and communication technology. Data were imported into Excel 2013 software. Results: Both hospitals were unacceptable in terms of compliance with the Ministry of Health standards. In terms of human resources and information and communication technology, both hospitals were at an unacceptable level. In terms of hoteling indicator and general conditions, both hospitals were moderate, and in terms of process indicators, one hospital was at medium level and another was at unacceptable level. Conclusion: Compliance with national standards developed by the Ministry of Health, and planning to provide resources for hospitals authorities seeking to enter the medical tourism industry seem essential.   Keywords: Readiness, Single-specialty hospital, International patient, Medical tourism   Citation: Shaarbafchi Zadeh N, Niaraees Zavare AS, Najafi Shahkoohi A, Maddahian B. The Readiness of Single-Specialty Hospitals in Isfahan to Attract Medical Tourists. Journal of Health Based Research 2018; 4(3): 301-15. [In Persian]